Rescaling Retail and Consumption in the Contemporary Barcelona Area - Carles Carreras i Verdaguer; Lluís Frago Clols; Eduard Montesinos Ciuró (Bollettino della Società Geografica Italiana)
Consumption is one of the less know variable in urban studies. The article presents a general overview of Catalan and Barcelona study case, summarizing almost thirty years of research, with the goal to isolate the main contemporary trends of retail and consumption in the area. The recent economic processes in the Catalan context are analyzed in the first place. At the same scale, the level of analysis is again recentered on the changes into the metropolitan and regional Barcelona, focussing in the perspective of the old slogan of Catalonia-city. The necessity of the restructuration of the scale of the analysis is proposed. After, the lens is adjusted to the city of Barcelona case, focussing on the relevant change in his traditional centrality. Finally some future trends are advanced.